Analisis Faktor-Faktor Yang Mempengaruhi Permukiman Kumuh Ditinjau Dari Kriteria Kekumuhan Drainase (Studi Kasus: Desa Tanjung, Kecamatan Hamparan Rawang) - Herianja, Binta Oktry; Zaidir, Zaidir; Wardi, Wardi (Universitas Batanghari Jambi, 2024)
Based on the Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia Number 14/PRT/M/2018 concerning Quality Improvement of Slum Housing and Slum Settlements. It is stated that slum housing is housing that has decreased the quality of its function as a dwelling, while slums are settlements that are not habitable due to building irregularity, high building density, and unqualified building quality and facilities and infrastructure. Conditions in Tanjung Village, Hamparan Rawang District, Sungai Full City. The condition of Tanjung village, Hamparan Rawang District, Sungai Full City, is classified as a slum, judging from environmental drainage, there are collapses in drainage channels, a lot of garbage is thrown and accumulates in drainage channels, reducing the effectiveness of drainage channels, the amount of development in the area, and other bad conditions. The purpose of this study is to find out what factors affect drainage slums in Tanjung Village, Hamparan Rawang District, Sungai Full City, look for dominant factors and find strategies to prevent or minimize the occurrence of drainage slums in Tanjung Village, Hamparan Rawang District, Sungai Full City for the present and the future. This study used quantitative methods by distributing questionnaires to respondents. The results of the research conducted there are 5 factors that affect drainage slums, namely the inability of drainage to drain water runoff, unavailability of drainage, disconnection with urban drainage systems, lack of maintenance of drainage, collapse of drainage.